Smart temperature control system for agriculture through personal computer by RS232 channel / Wan Mohd Zabidi Wan Muda - Wan Muda, Wan Mohd Zabidi (2003)
This is a project report describes a smart automatic temperature control for agricultural application and purposes. Buoyant by the announcement made by the Prime Minister in the most recent 2004 budget, which saw a substantial increase in the allocation for the agricultural sector, fanners in general can look forward to a brighter future with better opportunities. With the application of smart automatic temperature control, productivity and quality will be significantly increased; time and cost would be greatly reduced. The system has been designed as such that heat detection could be remotely done from the control room via a computer. The system is made up of hardware and software, interfaced by RS232 with Visual Basic, the basic programming language. This project only explains the hardware aspect of the system.